The Effect of Profitability and Leverage on Tax Avoidance in Property and Real Estate Companies Listed on the Indonesia Stock Exchange in 2018-2020 - Hardini Ariningrum; Murni Indah Sari (eCo-Buss, 2023)
The goal of this study is to determine how profitability and leverage affect tax evasion. Research of this kind is quantitative. Property and real estate businesses that were listed on the Indonesia Stock Exchange (IDX) between 2018 and 2020 make up the study's population. Purposive sampling, or the selection of samples based on specified criteria, was used in this investigation. Using the purposive sampling technique, 45 samples from 15 real estate and property enterprises were gathered. Descriptive statistical analysis, the traditional assumption test, multiple linear regression analysis, and hypothesis testing are the analytical techniques used, and SPSS version 25 is used to handle the data. The findings of this study show that the profitability variable and the leverage variable have no discernible effects on tax evasion.